Distribution patterns and determinants of the lens thickness-to-anterior chamber depth ratio in cataract patients - Zheng, Chunwen; Geng, Wenwen; Ma, Ruirui; Hao, Xiaoning; Niu, Yuling; Cao, Duanrong; Hu, Yijun; Jin, Ling (Frontiers in Medicine, 2025)
BackgroundThe lens thickness-to-anterior chamber depth (LT/ACD) ratio remains underexplored, despite its significance in optimizing cataract surgical outcomes and stratifying the risk of potential complications in aging populations.AimThis study aimed to investigate the distribution patterns and determinants of the LT/ACD ratio in cataract patients.MethodsBilateral ocular biometrics of 715 cataract patients were measured using Lenstar LS-900. The LT/ACD ratios of the right and left eyes were analyzed separately, with the results for the left eyes used to validate those for the right eyes. The LT/ACD ratio was compared using the Mann–Whitney or Kruskal–Wallis test. Spearman’s correlation coefficients were used to evaluate its correlation with other biometrics. Univariable and multivariable linear regression analyses were performed to identify the determinants of the LT/ACD ratio.ResultsThe LT/ACD ratio was higher in women, in patients with shorter axial length (AL), and in older patients (all p < 0.0001). In both eyes, the LT/ACD ratio correlated with iris center distance, pupil size (PS), angle kappa, AL, and white-to-white corneal diameter (WTW) (all p < 0.05). Determinants of the LT/ACD ratio in the right eyes included age (β = 0.01), sex (β = −0.08), anterior corneal astigmatism (ACA) (β = 0.06), angle kappa (β = 0.30), and AL (β = −0.09). In the left eyes, determinants included age (β = 0.01), sex (β = −0.08), corneal curvature (CR) (β = −0.05), angle kappa (β = 0.20), AL (β = −0.12), and WTW (β = −0.12).ConclusionThe distribution patterns of the LT/ACD ratio varied with sex, AL, and age, and the LT/ACD ratio correlated with similar but distinct determinants in both eyes. These findings help us better understand the interaction between LT and ACD in the eyes of cataract patients.